Project-Based Learning in the Education of Young Spanish Students in Physical Activity, Health, and Society (Impetus, 2026)
The present study examines the implementation of Project Based Learning (PBL) inthe subject Physical Activity, Health and Society, within the Spanish curriculum of thesecond year of Bachillerato. The research was carried out in a public school locatedin a rural setting in southern Andalusia (Spain) and involved 38 students enrolled inthe subject (15 boys and 23 girls). A qualitative analysis was used. The results reflect amostly positive perception on the part of the students, highlighting the diversity of activities,collaborative work and participatory methodology as key factors in the learningprocess. Likewise, PBL showed a significant impact on the development of social andcivic competencies, favoring active involvement and autonomy. However, it is necessaryto improve: time management, availability of resources and students’ attitude.Despite these challenges, teacher intervention played an essential role in creating apositive learning environment, contributing to student motivation and engagement.In conclusion, the findings support the suitability of PBL in Physical Education in thebaccalaureate, although it is necessary to optimize its planning to maximize its effectivenessand sustainability in future implementations.
Keywords: Project-Based Learning; Physical Education; Competencies